Isolation of Primary Mouse Pulmonary Microvascular Endothelial Cells and Generation of an Immortalized Cell Line to Obtain Sufficient Extracellular Vesicles - Liu, Xu; Xia, Feiping; Wu, Xiao; Tang, Ying; Wang, Lu; Sun, Qin; Xue, Ming; Chang, Wei; Liu, Ling; Guo, Fengmei; Yang, Yi; Qiu, Haibo (Frontiers in Immunology, 2021)
Pulmonary microvascular endothelial cells (PMECs) and the extracellular vesicles (EVs) derived from PMECs participate in maintaining pulmonary homeostasis and mediating the inflammatory response. However, obtaining a high-purity population of PMECs and their EVs from mouse is still notoriously difficult. Herein we provide a method to isolate primary mouse PMECs (pMPMECs) and to transduce SV40 lentivirus into pMPMECs to establish an immortalized cell line (iMPMECs), which provides sufficient quantities of EVs for further studies. pMPMECs and iMPMECs can be identified using morphologic criteria, a phenotypic expression profile (e.g., CD31, CD144, G. simplicifolia lectin binding), and functional properties (e.g., Dil-acetylated low-density protein uptake, Matrigel angiogenesis). Furthermore, pMPMEC–EVs and iMPMEC–EVs can be identified and compared. The characteristics of pMPMEC–EVs and iMPMEC–EVs are ascertained by transmission electron microscopy, nanoparticle tracking analysis, and specific protein markers. iMPMECs produce far more EVs than pMPMECs, while their particle size distribution is similar. Our detailed protocol to isolate and immortalize MPMECs will provide researchers with an in vitro model to investigate the specific roles of EVs in pulmonary physiology and diseases.